Early oral language precursors of different types of reading difficulties in a consistent orthography - Grigorakis, Ioannis; Kargiotidis, Apostolos; Mouzaki, Angeliki; Manolitsis, George (Frontiers in Education, 2022)
The present longitudinal study examined whether early oral language skills of Greek-speaking children assessed in Grade 1 can predict the type of reading difficulties (RD) in Grade 2.Sixty-six typically developing (TD) children and eighty-seven children with RD were assessed on phonological awareness (PA), morphological awareness (MA), rapid automatized naming (RAN), and vocabulary in the mid of Grade 1. Children were classified in the two groups based on whether they scored consistently low (below the 25th percentile) or typically (above the 25th percentile) on standardized measures of text-reading fluency and reading comprehension at the end of Grade 1 and the beginning of Grade 2. Next, children with RD were assigned in two subgroups: first group included children (N=28) with predominantly reading fluency difficulties (RFD) and the second group included children (N=59) with single reading comprehension difficulties (RCD). A series of binomial logistic regressions showed that children’s classification in an RD group than a TD group was predicted by PA, RAN, and vocabulary achievement. Subsequent multinomial logistic regressions indicated that vocabulary, PA, and MA predicted children’s classification in the RCD subgroup than in the TD group. Furthermore, lower PA levels and higher RAN score predicted the classification of children in the RFD group than in the RCD or the TD group. These findings highlight the contribution of early oral language assessment to the identification of children with RD and specific types of RD. Theoretical implications for the role of oral language to reading will be discussed as well as practical implications for implementing customized interventions to match children’s educational needs on specific oral language deficits.